Outlaw Heroes in Myth and History - Seal, Graham (Anthem Press, 2011)
About This Book‘A wide-ranging account of the compelling power of the outlaw along the borders of history and mythology.’ —Professor Stephen Knight, University of Cardiff‘This is a ground-breaking and masterly work. Outlaw heroes and their myths have always been with us, celebrated by the people but often ignored by historians. This book examines the historical phenomenon of the outlaw from a global perspective, and in the process offers a rich insight into the significance of outlaws in society. Formidably researched, it reaches across cultures, gender and generations, from Robin Hood to Ned Kelly, Phoolan Devi and Osama bin Laden.’ —Dr John McQuilton, University of Wollongong‘In this splendid book, Professor Seal sifts the material for understandings of how sociological and psychological factors interact with each other in outlaw lore. He considers the tragic events and the human predicaments, and brings under the lens of scholarship a world dramatic and romantic, but also illusionary and sad.’ —Professor Dáithí Ó hÓgáin, University College Dublin‘Folklorist Seal examines the durability of the outlaw as hero in the imaginations of the disenfranchised. [...] Particularly valuable is the book’s final half, where Seal crafts a structural analysis outlining the cycle by which social and cultural circumstances transform the bandit into outlaw hero. Recommended.’ —M. L. Murray, Kean University, ‘Choice’This book is an overview and analysis of the global tradition of the outlaw hero. The mythology and history of the outlaw hero is traced from the Roman Empire to the present, showing how both real and mythic figures have influenced social, political, economic and cultural outcomes in many times and places. The book also looks at the contemporary continuations of the outlaw hero mythology, not only in popular culture and everyday life, but also in the current outbreak of global terrorism. The book also presents a more general argument related to the importance of understanding folk and popular mythologies in historical contexts. Outlaw heroes have a strong purchase in high and popular culture, appearing in film, books, plays, music, drama, art, even ballet. To simply ignore and discard such powerful expressions without understanding their origins, persistence and especially their ongoing cultural consequences, is to refuse the opportunity to comprehend some profoundly important aspects of human behaviour. These issues are pursued through discussion of the processes through which real and mythical outlaw heroes are romanticised, sentimentalised, sanitised, commodified and mythologised. The result is a new position in the continuing controversy over the existence the ‘social bandit’ that highlights the central role of mythology in the creation and perpetuation of outlaw heroes.Readership: This book will be of use to academics of anthropology, history, politics and criminology, and anyone interested in bandits and their effect on contemporary society.